Strategic Blade Shape Optimization for Aerodynamic Performance Improvement of HAWT - Kim, You Jin; Al-Abadi, Ali Kedher Kashin; Delgado, Antonio (Proceedings of ASME International Mechanical Engineering Congress and Exposition, 2016)
This study introduces strategic methods for improving the aerodynamic performance of wind turbines. It was completed by combining different optimization methods for each part of the wind turbine rotor. The chord length and pitch angle are optimized by a torque-matched method (TMASO), whereas the airfoil shape is optimized by the genetic algorithm (GA). The TMASO is implemented to produce an improved design of a reference turbine (NREL UAE Phase V). The GA is operated to generate a novel airfoil design that is evaluated by automatic interfacing for the highest gliding ratio (GR). The adopted method produces an optimized wind turbine with an 11% increase of power coefficient (Cp) with 30% less of the corresponding tip speed ratio (TSR). Furthermore, the optimized wind turbine shows reduced tip loss effec
UnivIS-Import:2016-06-01:Pub.2016.tech.ITC.stmmec.strate